Airway Remodeling in Mouse Models of Exposure to Allergen - Hirota, Jeremy (My University, 2009)
Asthma is .a respiratory.,disease.that affects over 300 million people world-wide and is involved in over 250000 deaths annually. Asthma is classically thought of as an allergic disease with variable airflow obstruction and airway hyperresponsiveness (AHR) associated with airway remodeling, although phenotype variations are observed in the population. Due to multiple factors including genes, gender, exposure to pathogens, environmental pollutants, diets, and obesity, a clear picture of the complex interactions between an individual's genes, the environment which they live in, and the development of an asthmatic phenotype remains elusive. Despite the availability of treatment strategies for asthma, varying degrees of airway inflammation, remodeling, and AHR remain present in an asthmatic patient. Our general hypothesis that was the basis for all studies was the following: "Airway remodeling in response to allergen exposure is a major contributing factor to AHR observed in asthmatics. Understanding the mechanisms behind the different components of airway remodeling will provide new avenues for therapeutic development aimed at improving lung function above and beyond current treatment strategies." The currently available therapeutics and management strategies for asthma are unable to prevent or reverse components of airway remodeling. It is possible that with greater understanding of the processes involved in the various indices of airway remodeling new classes of therapeutics could be developed to selectively target this broad, ill-managed aspect of asthma. Collectively the studies contained in this thesis have been linked by the general themes of greater characterization of in vivo mouse models of allergen exposure, the application of these models to mechanistically explore the biological pathways involved in the different components of airway remodeling, and the testing of novel therapeutic strategies targeting these pathways of interest.
Keywords: airway; remodel; mouse; allergen